Radiotherapy versus no radiotherapy for rectal neuroendocrine carcinoma patients treated with surgery and chemotherapy: a population-based cohort study - Xiaojun Liu; Jiaying Li; Farooq Benish; Shuping Li; Weisheng Zhang (Discover Oncology)
Abstract Background Chemotherapy is regularly recommended for surgically rectal neuroendocrine carcinoma (NEC) patients. However, the additional benefit of perioperative radiotherapy for these patients is unclear to date. This study aims to evaluate the outcome of radiotherapy in rectal NECs who treated with surgery and chemotherapy. Methods This is a retrospective controlled study based on SEER database. Propensity score matching (PSM) was applied to reduce the baseline bias. Rectal NECs who underwent surgical resection plus chemotherapy with or without radiotherapy were extracted from SEER database. According to whether receiving radiotherapy, patients were divided into two cohorts: radiation treatment (RT) group and non-RT group. Overall survival (OS) was measured to assess the clinical benefits of RT. Kaplan–Meier survival analysis, univariable and multivariable regression analysis were applied. Results A total of 666 eligible patients were finally enrolled. The difference in OS remained significant both before and after PSM. Subgroup analyses revealed significantly better results for stage II, III and even IV patients who received radiotherapy whether before or after matching (all p < 0.05). The multivariable analysis showed that radiotherapy was associated with OS (HR 0.54; 95% CI 0.45 to 0.65; p < 0.001), together with distant metastasis. These results were consistent after matching (both p < 0.05). Conclusions ​Radiotherapy was an independent favorable prognostic factor for rectal NECs. The addition of radiotherapy to surgery plus chemotherapy might improve the clinical outcome. In the future, well-designed prospective studies are needed to assess the potential role of radiation in managing surgically resectable rectal NEC.